Why so negative? Exploring the socio-economic impacts of large carnivores from a European perspective. (March 2021) - Rode, Julian; Flinzberger, Lukas; Karutz, Raphael; Berghöfer, Augustin; Schröter-Schlaack, Christoph
Abstract: With populations of wild carnivores growing in Europe, public debates on human-wildlife conflicts are becoming polarized around economic damages and risks to human safety. This article explores the state of knowledge on the broader socio-economic impacts of four European large carnivore species (wolf, bear, lynx and wolverine). We have developed a comprehensive categorization of the socio-economic impacts of large carnivore presence, combining impact assessment approaches from project planning with a conceptualization of biodiversity values (e.g. Nature's Contributions to People). We distinguish 19 impact categories grouped according to 1) economic impacts, 2) health and well-being impacts, and 3) social and cultural impacts. A review of the academic literature since 1990 identified 82 articles that assessed the socio-economic impacts of the four European large carnivore species, 44 of which focused on Europe and 33 on North America. Our analysis of these articles reveals a bias towards investigations of negative economic impacts, in most cases of wolves. To contrast the information provided by science with perspectives from conservation practice, we conducted a survey among expert practitioners to elicit relevance ratings for the impact categories. Several categories considered relevant by the survey respondents are underrepresented in the academic literature. These include, in particular, positive impacts: benefits from wildlife tourism and commercial activities, benefits from game population control by large carnivores, benefits from regional and product marketing, cultural heritage and identity, educational and research benefits, and social cohesion. This incongruity between supply and demand for scientific information likely reinforces biased public debates and the negative public perception of large carnivores. We recommend a stronger research focus on the socio-economic benefits of large carnivores, drawing on diverse impact metrics.